Studies on entry events of porcine epidemic diarrhea virus (PEDV) - Changin, Oh (Kansas State University, 2020)
Coronaviruses are currently the most serious public health concern. The new outbreak of coronavirus disease 2019 (COVID 19) represents a pandemic threat, which led to being declared a Public Health Emergency of International Concern (PHEIC) by the World Health Organization (WHO). The first US outbreak of porcine epidemic diarrhea virus (PEDV) in 2013 and its subsequent spreading to European and Asian countries raised significant economic and public health concerns worldwide. Thus, the development of coronavirus vaccines and therapeutics are urgently needed. Detailed studies on the entry event of coronaviruses may contribute to developing novel therapeutic targets for coronavirus infection. Most cell culture adapted PEDV replication requires the addition of protease in the medium, but the mechanism of protease in PEDV infection is not well demonstrated. Thus, we examined the role of protease during the entry of PEDV using two different proteases-adapted PEDV US strains, PEDV KD and AA. Our study showed that the activity of protease was required at an early stage of PEDV KD replication, particularly after virus binding to cells. The addition of protease facilitated the escape of viruses from the endosome to the cytoplasm leading to a successful replication. The host endosomal protease and endosomal maturation were also shown to be important in the endosomal escape of PEDV by demonstrating endosomal retention of PEDV KD or AA in the presence of inhibitors of cathepsins or endosomal acidification. We also explored the roles of the acid sphingomyelinase (ASM)/ceramide pathway in the entry of PEDV. The infection of PEDV 8aa in Vero cells induced ceramide formation mediated by ASM activation. The inhibition of ASM significantly reduced the replication of 8aa by inhibiting viral endosomal escape. These results demonstrated the importance of interactions among viruses, host cells, and proteases during coronavirus entry for successful replication. During further examination of PEDV and host cell interaction, we observed that protease independent PEDV 8aa infection in Vero cells led to apoptotic cell death. Caspase 6 or 7 cleaved viral nucleocapsid(N) protein at the late stage of the replication while the cells were undergoing the apoptotic process. The caspase-mediated cleavage occurred between D⁴²⁴ and G⁴²⁵ near the C-terminal of N protein. Addition of a pan-caspase inhibitor to prevent the N protein cleavage significantly increased 8aa replication. In conclusion, the achievement of endosomal escape is a crucial step in the PEDV life cycle. The addition of the exogenous protease facilitates the endosomal escape of protease adapted PEDV strains. Activation of ASM/ ceramide pathway led to the efficient replication of protease independent PEDV by facilitating the endosomal escape of the virion. During protease independent PEDV replication, host cells activate caspase-mediated apoptosis as a defense mechanism. These in-depth understandings will provide clues for developing potential PEDV and coronavirus therapeutic targets.
Keywords: Porcine Epidemic Diarrhea Virus; Virus entry; Ceramide; Exogenous and endogenous protease; Endosomes; Apoptosis